Arquivos fluviais tecnogênicos na Serra do Espinhaço Meridional: influências antrópicas na configuração do vale do Ribeirão Datas - Alessandra de Abreu Andrade (2024)
This dissertation presents the results of a study carried out with the aim of investigating the influence of anthropogenic activities on the generation of deposits and the configuration of the Datas river valley, in the Diamantina micro-region, between the towns of Gouveia and Datas. Thus, the research intersects the fields of Fluvial Geomorphology and Anthropocene/Technogenic studies, focusing on the interpretation of fluvial morphologies and depositional successions. The need for this study arose from an initial observation about the lack of research that contextualizes the discussion of technogenesis and its implications in an environment historically occupied by various anthropogenic activities, mainly alluvial mining. The Ribeirão Datas basin is located in the Serra do Espinhaço Meridional and the main drainage is 34 km long, covering 123 km² up to the confluence with the left bank of the Ribeirão Chiqueiro. The investigation focused on the valley floor and its river archives, and was divided into three sections: the lower course (near the confluence with the Chiqueiro stream), the middle-high course (near the urban perimeter of Datas) and the upper course (rural region of the municipality of Datas). The methodology used includes a survey of the occupation history of the Serra do Espinhaço Meridional, the application of a technogenic terrain mapping proposal, the description and interpretation of fluvial depositional successions, temporal analysis using satellite images and aerophotos (1965-2021) and a geochronological survey using Optically Stimulated Luminescence (OSL) dating. The results revealed that the three stretches visited have characteristics, mainly in the plain (P) and on the terrace (T1), such as the clogging and piling up of poorly selected sediments, the presence of erosive features such as excavations, artificial ponds and bed detour, which indicate secular and modern anthropogenic origin. The stratigraphic interpretation of the profiles surveyed indicates that anthropogenic action, added to the hydrosedimentary dynamics of the watercourse, was able to reconfigure the deposits of the fluvial levels surveyed in the valley floor, mostly containing important erosive discordances and an abundance of poorly selected bed material rich in sandy bed depositional structures. The ages obtained by LOE vary between 145 ± 10 years and 16,260 ± 1,600 years, extrapolating the limit of the occupation history in the area. Based on these results, it should be noted that analyzing the implications of morphotechnogenesis based on fluvial archives proved to be a complex task, given that various types of anthropogenic activities are currently present in the alluvial valley, which can rework areas that have already been modified in the past, and that the dynamics of the environment can impact each stretch of the valley differently. In addition, the application of LOE in this context presented important limitations, making it difficult to obtain a solid chronology for the evolutionary processes in the valley over the last few centuries and decades.